Investigation of heat transfer characteristics of high-altitude intercooler for piston aero-engine based on multi-scale coupling method. (August 2020) - Liu, Zhentao; Sun, Meiyao; Huang, Yuqi; Li, Keyang; Wang, Chongjun
Highlights: Multi-scale coupling is used for 87.05% improved accuracy than the existing method. The effect law of altitude on heat transfer efficiency is studied. The changes in heat transfer in/below the stratosphere are separately discussed. Formula for the dependency of heat exchanger efficiency on height is developed. Abstract: Altitude affects the heat exchange capacity of a heat exchanger, which in turn affects the performance of an aircraft with piston engines. In order to study this mechanism of influence and the associated principles, a three-dimensional computational fluid dynamics (CFD) simulation of an intercooler is conducted based on multi-scale coupling. The simulation results have a high degree of coincidence with the test data on ground, with maximum error of no more than 10%. The simulation height is then extended to an altitude of 20 km. It is found that before the aircraft enters the stratosphere, the overall efficiency of the intercooler decreases by 1.98% on average for every 1km increase in the altitude and decreases by 3.26% when the height is above 11 km. The heat transfer capacity of the intercooler is gradually enhanced owing to the gradually increasing temperature difference while atmospheric density is relatively large. After entering the stratosphere, the external temperature stops changing; the density decreases to 1/14 of the value at the ground, and the low density becomes the dominant factor, resulting in reduced heat transfer coefficient. Finally, an empirical formula for the overall heat exchange efficiency of the intercooler as a function of the altitude is proposed.